2017
DOI: 10.1186/s12872-017-0705-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life questionnaire predicts poor exercise capacity only in HFpEF and not in HFrEF

Abstract: BackgroundThe Minnesota Living with Heart Failure Questionnaire (MLHFQ) is the most widely used measure of quality of life (QoL) in HF patients. This prospective study aimed to assess the relationship between QoL and exercise capacity in HF patients.MethodsThe study subjects were 118 consecutive patients with chronic HF (62 ± 10 years, 57 females, in NYHA I-III). Patients answered a MLHFQ questionnaire in the same day of complete clinical, biochemical and echocardiographic assessment. They also underwent a 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
0
15
0
1
Order By: Relevance
“…Chronotropic incompetence is present in 33–77% of HFpEF patients, 188 , 189 and defined as the failure to reach 70–80% 188–190 of the predicted maximal heart rate. Reduced heart rate recovery after exercise has prognostic value 191–193 . Reduced exercise capacity can be defined as a peak workload ≤75% of the value predicted for age.…”
Section: The New Heart Failure Association Diagnostic Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronotropic incompetence is present in 33–77% of HFpEF patients, 188 , 189 and defined as the failure to reach 70–80% 188–190 of the predicted maximal heart rate. Reduced heart rate recovery after exercise has prognostic value 191–193 . Reduced exercise capacity can be defined as a peak workload ≤75% of the value predicted for age.…”
Section: The New Heart Failure Association Diagnostic Recommendationsmentioning
confidence: 99%
“…Reduced heart rate recovery after exercise has prognostic value. [191][192][193] Reduced exercise capacity can be defined as a peak workload ≤75% of the value predicted for age. In elderly patients with suspected HFpEF a 6-minute walk test (6MWT)…”
Section: Exercise Testsmentioning
confidence: 99%
“…(30) Previous studies assessing the associations between CVRF and comorbidities with peak VO2 were performed in much smaller populations and, possibly as a consequence, only found some of these factors to be significant. (31,32) Reference ranges…”
Section: Predictors For Peak Vo2mentioning
confidence: 99%
“…3,10 Despite the positive effects of exercise training on outcomes, only about 30% of the HF patients adhere to their exercise recommendations. 11 Several factors are related to the exercise capacity of HF patients, 12,13 including symptoms of anxiety, depression, and cognitive impairment 12,[14][15][16][17][18] ; however, their roles remain unclear, and the study results are inconsistent. With regard to anxiety, some studies have found that a higher anxiety level is associated with a lower exercise capacity in HF patients, 17 but other studies have not confirmed this.…”
Section: Introductionmentioning
confidence: 99%